From The Micro To The Macro Scale: A Textural And Chemical Perspective Of Characterizing Waste-Rock Material - S. Diehl; P. Hageman; D. Fey; H. Lowers (Society for Mining, Metallurgy & Exploration, 2007)
Understanding relationships between mineralogy, texture, microstructural features, and element distribution and residence in minerals, is critical for accurate modeling of mineral weathering in waste-rock piles. The morphology of minerals and deformation structures, such as veins and faults, are important factors that control: (1) fluid access to the mineral surface to initiate dissolution, (2) the distribution of trace elements, and (3) formation of secondary minerals. We characterized the mineralogy, textures, and chemical properties of waste-rock material at three sites at scales ranging from outcrop to micrometer scale. A comprehensive hand-sample to thin-section scale methodology utilizing light microscopy, scanning electron microscopy, electron microprobe, and laser ablation ICP-MS was used to thoroughly characterize the waste-rock material.